Are remittances a "catalyst" for financial access? Evidence from Mexican household data - Christian Ambrosius (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2012)
In policy discussions, it has frequently been claimed that migrants' remittances could function as a catalyst for financial access among receiving households. This paper provides empirical evidence on this hypothesis from Mexico, a major receiver of remittances worldwide. Using the Mexican Family Life Survey panel (MxFLS) for 2002 and 2005, the results from the fixed effects logit model show that receiving remittances is strongly correlated with the ownership of savings accounts and, to some degree, with the availability of borrowing options. These effects are more important for rural households than for urban households and are more important for microfinance institutions, than for traditional banks.
Keywords: G21; O16; F24; 330; Remittances; Mexico; Financial Access; Microfinance; Rücküberweisung (Migranten); Privater Haushalt; Finanzierung; Mikrofinanz; Mexiko